KECERDASAN LINGUISTIK PADA BUKU PEMBELAJARAN TEMATIK KELAS 1 KURIKULUM 2013 - Rizki Ramadhan; Ahmad Asrof Fitri (Al-mujahidah, 2023)
The background of this study departs from the fact that learning activities carried out in schools in Indonesia in general have not been able to determine the appropriate learning methods for students. One solution is to determine the right learning method by knowing the concept of Linguistic intelligence in Core Competencies and Basic Competencies. This study aims to describe the concept of linguistic intelligence in Thematic class 1 learning book 2013 curriculum based on Core and Basic Competencies, and to know Linguistic Intelligence in Thematic learning book class 1 curriculum 2013. Research data is sourced from library data because this research is a Library Research. There are two kinds of data sources, namely primary data and secondary data. Primary data is 2013 Curriculum Thematic Class 1 subjects. Secondary data is in the form of books that talk about intelligence ever written by experts, can be magazines, journals, papers, internet and so on that have relevance to the title of the research. Data analysis uses descriptive qualitative analysis. The results showed that in the 2013 curriculum in thematic learning class 1 contained Linguistic intelligence based on the applicable curriculum in accordance with the core competencies and basic competencies to be achieved. In the Thematic learning book class 1 curriculum 2013 there is linguistic intelligence based on learning activities.